Multiplikasi Anggrek (Dendrobium sp var Kumala) Menggunakan Kombinasi Benzyl Amino Purin (BAP) dan Air Kelapa (Cocos nucifera L) Secara In Vitro - Nenden Nur Amalia; Ayuni Adawiyah; Ateng Supriyatna (UIN Sunan Gunung Djati Bandung, 2021)
Dendrobium sp. is one of the natural orchids in Indonesia. Optimization of media composition for in vitro orchid propagation is needed the multiplication ability and seed quality. The role of PGR in in vitro propagation of orchid plays role in triggering cell division, initiation, shoot growth, and the development of photomorphogenesis. The purpose of this study was to determine the effect of BAP and coconut water on the multiplication of Dendrobium sp. var kumalaorchids, and to determine the optimum concentration of BAP and coconut water on the multiplication of Dendrobium sp. var Kumala. This research was conducted with a single factor Completely Randomized Design (CRD). The treatment tested was the addition of BAP into MS0 media with 3 concentration levels (0,5; 1; 1,5 ppm), combined with 3 concentration levelsof coconut water (100; 150; 200 ml/l), and MS0 medium without the addition of BAP and coconut water (control). Based on the results of the study, it can be seen that there is an effect of BAP concentration and coconut water on the multiplication of Dendrobium sp. var kumalaorchids. The composition of the media with a concentration of 1 ppm BAP combined with 100-150 ml/l coconut water showed optimal results in increasing the number and length of leaves, namely 1,467 ± 0,416 leaves and 0,142 ± 0,036 cm. In contrast to the emergence of orchid leaves, the highest yield was found in 0,5 ppm BAP treatment media combine with 200 ml/l coconut water, with the beginning of the emergence of new leaves occuring at 4 ± 1 DAI. The BAP treatment of 1,5 ppm combined with 200 ml/l coconut water resulted in a higher number of roots, namely 1,22 ± 1,349 pieces.